2017
DOI: 10.1111/ffe.12723
|View full text |Cite
|
Sign up to set email alerts
|

On the fatigue damage micromechanisms in Si‐solution–strengthened spheroidal graphite cast iron

Abstract: Graphite nodules in spheroidal graphite cast iron (SGI) play a vital role in fatigue crack initiation and propagation. Graphite nodules growth morphology can go through transitions to form degenerated graphite elements other than spheroidal graphite nodules in SGI microstructure. These graphite particles significantly influence damage micromechanisms in SGI and could act differently than spheroidal graphite nodules. Most of the damage mechanism studies on SGI focused on the role of spheroidal graphite nodules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…It is worth remarking that the present fatigue crack was grown under conditions that correspond to the mid Paris regime for the material considered [43]. For both ferritic and pearlitic SGIs, 2D microscopy observations indicate that the appearance of the crack surface is similar in the entire stable crack propagation regime [15], as well as at different fatigue ratios and maximum stress intensity factors [8]. Therefore, it is likely that some of the features of the crack identified in Figure 7 are characteristic of a rather wide range of stable crack propagation regimes.…”
Section: Morphology Of the Crackmentioning
confidence: 75%
See 1 more Smart Citation
“…It is worth remarking that the present fatigue crack was grown under conditions that correspond to the mid Paris regime for the material considered [43]. For both ferritic and pearlitic SGIs, 2D microscopy observations indicate that the appearance of the crack surface is similar in the entire stable crack propagation regime [15], as well as at different fatigue ratios and maximum stress intensity factors [8]. Therefore, it is likely that some of the features of the crack identified in Figure 7 are characteristic of a rather wide range of stable crack propagation regimes.…”
Section: Morphology Of the Crackmentioning
confidence: 75%
“…These appear to act as crack attractors [12], leading to a higher graphite fraction on the fracture surface than in the bulk of the material [13]. Also, a crack might or might not propagate depending on the presence of clusters of nodules near its tip [14], which seem to be associated with load shielding effects [15]. These facts suggest that an analogy exists with particle-reinforced metal-matrix composites, where it has been clarified that the crack growth, including the occurrence of shielding and anti-shielding phenomena, is driven by the particle-induced microstructural stress field [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth remarking that the present fatigue crack was grown under conditions that correspond to the mid Paris regime for the material considered [43]. For both ferritic and pearlitic SGIs, 2D microscopy observations indicate that the appearance of the crack surface is similar in the entire stable crack propagation regime [15], as well as at different fatigue ratios and maximum stress intensity factors [8]. Therefore, it is likely that some of the features of the crack identified in Figure 7 are characteristic of a rather wide range of stable crack propagation regimes.…”
mentioning
confidence: 75%
“…The qualitative impression is that the crack front is initially straight and splits up after encountering such large nodules, hence generating a step with step wall parallel to the crack growth direction. This observation, combined with the fact that the nodules act as crack attractors [12,15], allows formulating a hypothesis for the mechanisms of formation of these steps, which is schematized in Figure 11 (a). The idea is to consider a straight horizontal crack front that moves along the Z-axis (i) and, at a certain point, reaches a nodule (ii).…”
Section: Crack Step Formation Mechanismmentioning
confidence: 99%
“…In the work of Sujakhu et al, the fatigue damage micromechanisms of SSF DI have been carefully studied. Based on the experimental observations, it was found that the crack initiation is affected by the degenerated graphite particles and casting defects, while the crack propagation stage is characterized by the interface decohesion between the spheroidal graphite and the ferritic matrix.…”
Section: Introductionmentioning
confidence: 99%